Risalah fi al-Istihsan al-Khawd fi ‘Ilm al-Kalam Karangan Imam al-'Asy'ari: Terjemahan Teks - Ibrahim, Mohd Radhi; Mohd Junoh, Rawiyah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2003)
Although the importance of 'aqidah has been accepted as a fundamental belief for every Muslims, but the authority of 'Ilm al-Kalam in Islamic epistemological structure is still on debate. Therefore the view of Imam Abu Hassan al-'Asy'ari the founder of the school of Ash'arite and his defence of the 'Ilm al-Kalam is very important for contemporary scholars for a better understanding of the issue. As far as the issue is concerned this article tries to elaborate the view of Imam al-'Asy'ari towards the authority of 'Ilm al-Kalam through the translation of his book "Risalah Fi al-Istihsan al-Khawd fi 'Ilm al-Kalam."